(untitled) (Sains Humanika, 2021)
The objective of this paper is to analyze the sustainability of cash waqf (endowment) development in Indonesia from a quintuple perspective. Waqf can be in the form of productive assets (either current or fixed) or non-productive fixed assets. The method of this research uses qualitative research based on a literature review and in-depth interview with some top management of cash waqf management. Quintuple helix analysis is used to see relations among aspects which support waqf development. The result shows that cash waqf needs support from many aspects in order to maintain its sustainability. Knowledge creation and innovation from related aspects can strengthen the sustainable development of cash waqf in any form. Educational, economic and political systems are identified as important aspects which support sustainability